Business plan: Homestel Lisbon Boutique Hostel - Gouveia, Joana Isabel Gonçalves (2016)
Over the last few years Lisbon has been collecting numerous tourism awards, being recognized as one of the top destination cities. The present project aims to identify the feasibility of developing an accommodation establishment targeting flashpackers visiting Lisbon. For this purpose, public information available was collected from public data bases and data provided by market players and third party suppliers was analysed in order to understand Lisbon as a flashpacking tourism destination as well as how to develop a business plan and evaluate the implementation of an accommodation service establishment. After defining the business concept and strategy, all the required steps towards the Homestel implementation were performed in order to be possible to evaluate the business feasibility. Once all steps concluded, an economic and financial analysis was performed from which it was possible to conclude Homestel Project’s viability.